PENERAPAN ELECTRONIC GOVERNMENT MELALUI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI (SRIKANDI) DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PROBOLINGGO - Rahmah, Faizatur; meirinawati, meirinawati (Universitas Negeri Surabaya, 2023)
The increasingly complex development of digitalization makes the government continue to develop electronic government as a form of accelerating bureaucratic reform, it also applies to the digital archive management system. Digital archives form an electronic archival container, so that it can make it easier to access these information sources where, the disruptive era makes digital archives continue to develop, one of which is through an application called SRIKANDI (integrated dynamic archival information system) which is a general application in the field of archives. The purpose of this research is to describe the application of electronic government through an integrated dynamic archiving information system (SRIKANDI) at the Probolinggo City Library and Archives Office. This type of research uses qualitative research with a descriptive approach. This research analyzes the success of electronic government by Hafid (2017) which includes: Institutional Success Factor, Organizational Success Factor, Technological Success Factor. The results showed that the application of the SRIKANDI application at the Library and Archives Office has been running well and maximally. This is supported based on the success factors of implementing electronic government according to Hafid (2017). In the leader authority factor, a leader at the Probolinggo City Library and Archives Office strongly supports the application of the SRIKANDI application through the socialization of all internal employees of the office, then the SOP factor is still in the process of being prepared and using the Manual Book. The project management and financial factors have been running well and there are no problems with the budget. Furthermore, the technological infrastructure factor and technological expertise, the application of the SRIKANDI application is still lacking in support from technological infrastructure, while technological expertise already has employees whose basic knowledge is qualified to manage the SRIKANDI application as an admin.